PENGARUH PEMBELAJARAN BLANDED TERHADAP PEMAHAMAN KONSEPTUAL FISIKA MEKANIK MAHASISWA TEKNIK ELEKTRO UNIVERSITAS MUHAMMADIYAH JEMBER - Sofia Ariyani; Irawati Irawati; Nely Ana Mufarida; Setiyo Ferdi Yanuar (ScienceEdu, 2023)
PTM (face-to-face restrictions) makes elementary to high school education experience a less than optimal learning process; it has an impact on decreasing the understanding and maturation of subject concepts or courses by students. Face-to-face restrictions (PTM) make all educators make many changes to learning systems and methods so that they can fill the time from the lack of teaching materials. Based on the problem of declining conceptual understanding of basic mechanical physics, the author conducts research with models and develops blended learning concepts. The novelty of this research is based on the point of view of scope and time, so it is not just in applying online and offline learning. Based on the development of the blended learning design model, which is quite varied, the author tries to design and develop the Pannan and Legge design model. This blended learning design model is quite simple, namely combining online and offline learning. The results of research conducted by the author related to the blended learning method are 8 online meetings and 8 offline meetings. This learning method indicator uses a questionnaire conducted by the lecturer of the Basic Mechanical Physics course for students of the classes of 2018, 2019, 2020, and 2021. The results of the questionnaire on the total students of the classes of 2018, 2019, 2020, and 2021 are 82%, which means that 82% of students can accept the blended learning method with the Pannan and Legge models that have been carried out.